2019
DOI: 10.1111/jce.14152
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐lead electrocardiographic localization of idiopathic premature ventricular contraction origins

Abstract: The major sites of origins of idiopathic ventricular arrhythmias have been elucidated. Idiopathic ventricular arrhythmias most often present as premature ventricular contractions (PVCs) with a focal mechanism, and commonly occur without structural heart disease. Idiopathic ventricular arrhythmias usually originate from specific anatomical structures, commonly endocardial but sometimes epicardial and exhibit characteristic electrocardiograms (ECGs) based on their anatomical background. There are general and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 64 publications
(201 reference statements)
0
28
0
1
Order By: Relevance
“…An accurate prediction of RVOT and LVOT origins of OTVT can optimize the CA strategy, reduce ablation duration, and avoid operative complications. Previous studies (Kamakura et al, 1998;Hachiya et al, 2000;Ito et al, 2003;Joshi and Wilber, 2005;Tanner et al, 2005;Haqqani et al, 2009;Zhang et al, 2009;Betensky et al, 2011;Yoshida et al, 2011Yoshida et al, , 2014Cheng et al, 2013Cheng et al, , 2018Nakano et al, 2014;Efimova et al, 2015;He et al, 2018;Xie et al, 2018;Di et al, 2019;Enriquez et al, 2019;Yamada, 2019) propose several criteria or models to estimate RVOT and LVOT origins. However, these results have been limited by sample size, scope of studies, ECG measurement efficiency, and generalizability of the models.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate prediction of RVOT and LVOT origins of OTVT can optimize the CA strategy, reduce ablation duration, and avoid operative complications. Previous studies (Kamakura et al, 1998;Hachiya et al, 2000;Ito et al, 2003;Joshi and Wilber, 2005;Tanner et al, 2005;Haqqani et al, 2009;Zhang et al, 2009;Betensky et al, 2011;Yoshida et al, 2011Yoshida et al, , 2014Cheng et al, 2013Cheng et al, , 2018Nakano et al, 2014;Efimova et al, 2015;He et al, 2018;Xie et al, 2018;Di et al, 2019;Enriquez et al, 2019;Yamada, 2019) propose several criteria or models to estimate RVOT and LVOT origins. However, these results have been limited by sample size, scope of studies, ECG measurement efficiency, and generalizability of the models.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed relatively high accuracy for differentiating right from left OT‐VA origin on 12‐lead ECG algorithm 12‐15 . However, the accuracy of prediction varies according to the patient population because there is considerable variability in lead positions, shape of the chest wall, heart rotation, and conduction properties from person to person 16,17 . In general, since the LVOT is posteriorly positioned compared with the RVOT, PVC originating from the LVOT tends to show a larger and wider R‐wave at lead V 1 and V 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Relatively narrow QRS generally indicates septal origin or early entry to the preferential conduction fibres of the His-Purkinje system. Finally, signs of initial slow depolarisation would sug- gest an epicardial origin instead of the most common endocardial origin of the PVC (19). Globally, the most frequent location of PVCs is the RVOT, generally not related to any underlying cardiac disease.…”
Section: Clinical Presentationmentioning
confidence: 99%